2016
DOI: 10.1161/atvbaha.115.306552
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Longitudinal Associations of MBL, MASP-1, MASP-2, MASP-3, and MAp44 With Endothelial Dysfunction and Intima–Media Thickness

Abstract: 12associations with future CVD. When the effect of MBL on complications of established CVD was investigated, low MBL was in fact protective in most studies. [13][14][15] Thus, considerable discrepancy remains in the literature on whether MBL has beneficial or adverse effects in CVD.This reported discrepancy might be explained by a dual role of MBL in different etiologic aspects of CVD. Objective-Previous studies suggested that the lectin-complement pathway plays a complex role in cardiovascular disease (CVD). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Honda et al 54 demonstrated a close relationship between endothelial dysfunction evaluated by flow-mediated dilation and vascular inflammation detected by ( 18 F)-fluorodeoxyglucosepositron emission tomography/computed tomography in subjects with mild cardiovascular risks, both of which were improved after a 6-month antihypertensive treatment. In an observational cohort study, Hertle et al 55 also showed that a number of molecules involved in the lectin-component pathway may contribute to endothelial dysfunction in subjects with mild metabolic risk factors. Furthermore, a recent meta-analysis has shown a positive association between higher serum levels of IL-1 receptor antagonist and increased incidence of cardiovascular disease in the general population.…”
Section: Hallmark Of Disease Inflammationmentioning
confidence: 99%
“…Honda et al 54 demonstrated a close relationship between endothelial dysfunction evaluated by flow-mediated dilation and vascular inflammation detected by ( 18 F)-fluorodeoxyglucosepositron emission tomography/computed tomography in subjects with mild cardiovascular risks, both of which were improved after a 6-month antihypertensive treatment. In an observational cohort study, Hertle et al 55 also showed that a number of molecules involved in the lectin-component pathway may contribute to endothelial dysfunction in subjects with mild metabolic risk factors. Furthermore, a recent meta-analysis has shown a positive association between higher serum levels of IL-1 receptor antagonist and increased incidence of cardiovascular disease in the general population.…”
Section: Hallmark Of Disease Inflammationmentioning
confidence: 99%
“…The complement system has been implicated in cardiometabolic diseases, including the metabolic syndrome 47 , 61 , 62 . Complement activation is strongly associated with low-grade inflammation in the metabolic syndrome and related cardiometabolic diseases 63 70 . Notably, we have shown in observational studies in humans that activated complement factors are strongly associated with markers of endothelial dysfunction 64 , 65 , which are thought to reflect mainly greater microvascular endothelial dysfunction 10 .…”
Section: Novel Targets In the Metabolic Syndrome: Managing Dysfunctiomentioning
confidence: 99%
“…In a recent study investigating the associations of components of the lectin pathway and low-grade inflammation, endothelial dysfunction, carotid intima-media thickness and CVD, MASP-3 was associated with endothelial dysfunction, independent of plasma MBL 36 . The authors suggested a potential role through non-complement pathways.…”
Section: Discussionmentioning
confidence: 93%